2013
DOI: 10.1186/1472-6947-13-127
|View full text |Cite
|
Sign up to set email alerts
|

Effects of and satisfaction with short message service reminders for patient medication adherence: a randomized controlled study

Abstract: BackgroundMedication adherence is critical for patient treatment. This study involved evaluating how implementing Short Message Service (SMS) reminders affected patient medication adherence and related factors.MethodsWe used a structured questionnaire to survey outpatients at three medical centers. Patients aged 20 years and older who were prescribed more than 7 days of a prescription medication were randomized into SMS intervention or control groups. The intervention group received daily messages reminding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 27 publications
3
35
0
3
Order By: Relevance
“…Nevertheless, the overwhelming majority of quantitative studies of smartphones, such as Strandbygaard, Thomsen, and Backer (2010), Petrie, Perry, Broadbent, and Weinman (2012), Huang et al (2013), andFinistis, Pellowski, andJohnson (2014), are forced to focus on the simplest intervention that smartphones permit-text message reminders. The comprehensive surveys by Vervloet et al (2012) and Sarabi, Sadoughi, Orak, and Bahaadinbeigy (2016) concluded that there is robust evidence that text message reminders improve medication adherence, especially in chronic conditions or in patient populations requiring complex medication regimens, such as HIV, asthma, and diabetes.…”
Section: Improving Medication Adherence: Smartphone Resultsmentioning
confidence: 99%
“…Nevertheless, the overwhelming majority of quantitative studies of smartphones, such as Strandbygaard, Thomsen, and Backer (2010), Petrie, Perry, Broadbent, and Weinman (2012), Huang et al (2013), andFinistis, Pellowski, andJohnson (2014), are forced to focus on the simplest intervention that smartphones permit-text message reminders. The comprehensive surveys by Vervloet et al (2012) and Sarabi, Sadoughi, Orak, and Bahaadinbeigy (2016) concluded that there is robust evidence that text message reminders improve medication adherence, especially in chronic conditions or in patient populations requiring complex medication regimens, such as HIV, asthma, and diabetes.…”
Section: Improving Medication Adherence: Smartphone Resultsmentioning
confidence: 99%
“…Studies on text messaging as a way to enhance adherence to medications for noncancer diseases have shown effectiveness (Arora, Peters, Agy, & Menchine, 2012;Foreman et al, 2012;Halpern, Lopez, Grimes, & Gallo, 2011;Hardy et al, 2011;Huang et al, 2013;Lester et al, 2010;Lewis et al, 2013;Mbuagbaw et al, 2013;Pellowski & Kalichman, 2012;Petrie, Perry, Broadbent, & Weinman, 2012;Pop-Eleches et al, 2011;Rodrigues et al, 2012;Vervloet, 2012). A detailed review of the evidence for text messaging is provided elsewhere in this supplement (Spoelstra & Sansoucie, 2015).…”
Section: Sm Artphone Applicationsmentioning
confidence: 95%
“…Previous studies on satisfaction regarding medication reminders and health care appointment reminders also has shown satisfaction and acceptance for text message reminders by the participants [35][36][37].…”
Section: Principal Findingsmentioning
confidence: 83%